Exploring Grade VIII Students' Procedural Skills in Solving Pythagorean Problems - Ade Riska Sanjani; Achmad Salido; Akbar Nasrum; Chairuddin Chairuddin; Jahring Jahring; Dian Ulfa Sari (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2024)
This study explores the procedural skills of grade VIII students in solving Pythagorean Theorem problems, focusing on the diversity of problem-solving steps and error patterns that emerge. A descriptive qualitative method was used in this study, with three students selected as subjects based on high, medium, and low levels of mathematical ability. Data were collected through problem-solving tasks and semi-structured interviews to comprehensively understand the students' approaches and strategies. The results showed that students with high procedural skills implemented problem-solving steps in a structured manner, while those with moderate skills often needed to be more consistent in recording critical steps. Students with low skills tended to bypass procedural structures and proceed directly to solutions, leading to a higher rate of errors. Error patterns varied by students' mathematical ability levels: high-ability students made no errors, medium-ability students exhibited errors in illustrations and procedural consistency, and low-ability students struggled with writing expressions and fully implementing steps. These findings emphasize the need for instructional approaches tailored to students' skill levels, such as structured learning and scaffolding, to strengthen procedural skills. A follow-up study with a broader sample is recommended to validate these findings and assess the effectiveness of instructional strategies for enhancing students' procedural skills across various mathematical topics.